Genetically induced moderate inhibition of 20S proteasomes in cardiomyocytes facilitates heart failure in mice during systolic overload - Ranek, Mark J.; Zheng, Hanqiao; Huang, Wei; Kumarapeli, Asangi R.; Li, Jie; Liu, Jinbao; Wang, Xuejun (Journal of molecular and cellular cardiology, 2015)
The in vivo function status of the ubiquitin–proteasome system (UPS) in pressure overloaded hearts remains undefined. Cardiotoxicity was observed during proteasome inhibitor chemotherapy, especially in those with preexisting cardiovascular conditions; however, proteasome inhibition (PsmI) was also suggested by some experimental studies as a potential therapeutic strategy to curtail cardiac hypertrophy. Here we used genetic approaches to probe cardiac UPS performance and determine the impact of cardiomyocyte-restricted PsmI (CR-PsmI) on cardiac responses to systolic overload. Transgenic mice expressing an inverse reporter of the UPS (GFPdgn) were subject to transverse aortic constriction (TAC) to probe myocardial UPS performance during systolic overload. Mice with or without moderate CR-PsmI were subject to TAC and temporally characterized for cardiac responses to moderate and severe systolic overload. After moderate TAC (pressure gradient: ~40mmHg), cardiac UPS function was upregulated during the first two weeks but turned to functional insufficiency between 6 and 12weeks as evidenced by the dynamic changes in GFPdgn protein levels, proteasome peptidase activities, and total ubiquitin conjugates. Severe TAC (pressure gradients >60mmHg) led to UPS functional insufficiency within a week. Moderate TAC elicited comparable hypertrophic responses between mice with and without genetic CR-PsmI but caused cardiac malfunction in CR-PsmI mice significantly earlier than those without CR-PsmI. In mice subject to severe TAC, CR-PsmI inhibited cardiac hypertrophy but led to rapidly progressed heart failure and premature death, associated with a pronounced increase in cardiomyocyte death. It is concluded that cardiac UPS function is dynamically altered, with the initial brief upregulation of proteasome function being adaptive; and CR-PsmI facilitates cardiac malfunction during systolic overload. •Systolic overload alters dynamically myocardial proteasomal performance.•Cardiac proteasome inhibition does not suppress cardiac hypertrophy responses.•Genetic cardiac proteasome inhibition promotes cardiac failure in systolic overload.•Cardiac proteasome inhibition promotes cardiomyocyte death during systolic overload.